Assessing heavy metal pollution and potential ecological risk of tea plantation soils - Zhao, Zuoping; Yan, Sha; Duan, Min; Fu, Jing; Wang, Qi; Liu, Zhifeng; Song, Fengmin; Tang, Bo; Li, Chen; Qin, Gongwei; et al. (International Journal of Agricultural and Biological Engineering, 2019)
Accumulation of heavy metals in agricultural soils tends to increase crop uptake of heavy metals, and can adversely impact human health through food chains. This study assessed the heavy metal pollution status and the potential ecological risk of tea plantation soils in southern Shaanxi Province, China. A total of 330 topsoil samples were collected to analyze the concentrations of seven heavy metals (Pb, Zn, Cu, Cr, Hg, As and Cd) and the pH level. The Hakanson potential ecological risk index was used based on the background levels of soil heavy metals in Shaanxi. Results showed that the averaged concentrations of soil Pb, Zn, Cu, Cr, Hg, As, and Cd were 10.0, 87.6, 16.4, 12.4, 0.2, 6.9 and 0.1 mg/kg, respectively. Cd and Hg concentrations exceeded level II of China’s Soil Environment Quality Standard (GB 15618–2009) in 9.3% and 7.0% of the total samples, respectively. The coefficient of variation ranged from 29.2% to 52.2% for different elements, and was 49.3% for Cd and 48.6% for Hg. The averaged comprehensive potential ecological risk index was 95.4, and the overall potential ecological risk was low, with 82.4% of the total samples at a low level of potential ecological risk. Cd and Hg contributed most to the potential ecological risk (35.5% and 46.5%, respectively), and the risks associated with other elements were relatively minor. This study suggested that soil Cd and Hg pollution should be controlled to ensure the safe production of tea in the study area. Keywords: ecological risk, heavy metal, soil pollution, tea plantation DOI: 10.25165/j.ijabe.20191206.4363 Citation: Zhao Z P, Yan S, Duan M, Fu J, Wang Q, Liu Z F, et al. Assessing heavy metal pollution and potential ecological risk of tea plantation soils. Int J Agric & Biol Eng, 2019; 12(6): 185–191.